2014
DOI: 10.1021/es503477q
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Low-NOx and High-Burnout Deep-Air-Staging Combustion under Real-Furnace Conditions in a 600 MWe Down-Fired Supercritical Boiler by Strengthening the Staged-Air Effect

Abstract: A 600 MW(e) down-fired pulverized-coal supercritical boiler, which was equipped with a deep-air-staging combustion system for reducing the particularly high NOx emissions, suffered from the well-accepted contradiction between low NOx emissions and high carbon in fly ash, in addition to excessively high gas temperatures in the hopper that jeopardized the boiler's safe operations. Previous results uncovered that under low-NOx conditions, strengthening the staged-air effect by decreasing the staged-air angle and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
(58 reference statements)
0
16
0
Order By: Relevance
“…Kuang et al 29 put forward a deep‐air‐standing low‐NO x combustion technology (i.e., multiple‐injection and multiple‐staging combustion technology, abbreviated as MIMSCT) for sharply reducing NO x and improving the severely asymmetric combustion. Its industrial application in a 600 MW e furnace confirmed that, in comparison to the same‐grade MBEL furnace suffering from asymmetric combustion, high carbon content in fly ash of 8.5%, and high NO x emissions of 1,467 mg/m 3 (6% O 2 ), the MIMSCT exhibited superiority in regulating symmetrical combustion and apparently lowering NO x , with NO x levels of 867 mg/m 3 (6% O 2 ) and carbon content in fly ash of 5.4% 30–32 …”
Section: Introductionmentioning
confidence: 80%
“…Kuang et al 29 put forward a deep‐air‐standing low‐NO x combustion technology (i.e., multiple‐injection and multiple‐staging combustion technology, abbreviated as MIMSCT) for sharply reducing NO x and improving the severely asymmetric combustion. Its industrial application in a 600 MW e furnace confirmed that, in comparison to the same‐grade MBEL furnace suffering from asymmetric combustion, high carbon content in fly ash of 8.5%, and high NO x emissions of 1,467 mg/m 3 (6% O 2 ), the MIMSCT exhibited superiority in regulating symmetrical combustion and apparently lowering NO x , with NO x levels of 867 mg/m 3 (6% O 2 ) and carbon content in fly ash of 5.4% 30–32 …”
Section: Introductionmentioning
confidence: 80%
“…As mentioned previously, aiming at the compatibility problem of strengthened low-NO x combustion and high burnout, CLHC is developed based on our group’s many years of work on W-shaped flame furnaces and the application experience gained from several stages of the prior MIMSCT. In order to confirm the CLHC’s high-burnout and low-NO x combustion advantages compared with the prior arts, the 600 MW e supercritical MIMSCT W-shaped flame boiler furnace involved in the previous work ,, was selected to perform both industrial-size measurements and numerical simulations at normal full-load operation. The subsequent efforts were devoted to numerical simulations of the gas/particle flow, coal combustion, and NO x formation of the furnace with CLHC.…”
Section: Methodsmentioning
confidence: 99%
“…The horizontal staged air and inclined OFA (fed into the primary combustion and burnout zones, respectively) are used to regulate the third and fourth stages of airflow injection and deepen the air-staging conditions. This deep-air-staging combustion layout is based on the so-called multiple-injection and multiple-staging combustion technology (MIMSCT), whose detailed description has already appeared in the literature. , Table lists the furnace’s conventional operation parameters mainly in the airflow and fuel supplying at full load.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, coal is the most polluting fossil fuel. Due to increasing environmental concerns, development of clean coal technologies, e.g., low NOx combustion (Kuang et al, 2014;Lv et al, 2010) and oxy-coal combustion for carbon capture and storage (CCS) (Bu et al, 2015), becomes more and more important. To develop clean coal technologies, a comprehensive understanding of pulverized-coal combustion physics is necessary.…”
Section: Introductionmentioning
confidence: 99%